ESTETISISME DAN DILEMA PEMBERDAYAAN PEREMPUAN DALAM IKLAN - Pranata, Moeljadi (Nirmana, 2001)
The development in women%5C%27s role is constructed by ads%5C%27 aestheticism and women%5C%27s attitude. Aestheticism provokes bad taste advertisement reducing woman as a mere biological object. Capitalistic system and structure has encouraged women to compete in social arena and subordination of women by men as well as conflicts among women. The empowerment of women%5C%27s role in ads can be achieved by generating the awareness on women not to part in stereotype establishing which inflicts women%5C%27s esteem. Further%2C law enforcement is required to control bad taste advertising. Abstract in Bahasa Indonesia : Perkembangan peran perempuan disebabkan oleh estetisisme iklan dan sikap perempuan sendiri. Estetisisme menyebabkan bad taste advertisement yang mereduksi perempuan sebatas mahluk biologis semata. Sistim dan struktur kapitalistik telah mendorong perempuan berkompetisi dalam arena sosial yang sekaligus menjadi ajang subordinasi perempuan oleh laki-laki serta ajang konflik antar perempuan. Pemberdayaan peran perempuan dalam iklan dapat dilakukan dengan gerakan penyadaran kepada perempuan agar tidak larut dalam proses pemapanan stereotipe yang merugikan perempuan. Selain itu%2C penegakan supremasi hukum perlu dilakukan untuk mengendalikan bad taste advertising. advertisment%2C+aestheticism%2C+empowerment%2C+women.